The Australian Temperament Project Generation 3 study: a population-based multigenerational prospective cohort study of socioemotional health and development. Issue 9 (16th September 2022) - Olsson, Craig A; Letcher, Primrose; Greenwood, Christopher J; McIntosh, Jennifer E; Barker, Sophie; Olsson, Catherine M; Macdonald, Jacqui A; Spry, Elizabeth A; Hutchinson, Delyse; Ryan, Joanne; Edwards, Benjamin; McGee, Rob; et al.
Abstract : Purpose: The Australian Temperament Project Generation 3 Study (ATPG3) was established to examine the extent to which offspring social and emotional development is shaped in the decades prior to conception, in parent and grandparent histories of psychosocial adjustment (eg, emotional regulation, relationship quality and prosociality) and maladjustment (eg, depressive symptoms, substance use and antisociality). Participants: The Australian Temperament Project (ATP) commenced in 1983 as a population representative survey of the social and emotional health of 2443 young Australians (Generation 2: 4–8 months old) and their parents (Generation 1). Since then, families have been followed from infancy to young adulthood (16 waves). Between 2012 and 2018, the cohort was screened biannually for pregnancies (Generation 3), with assessments conducted in the third trimester of pregnancy, and at 8 weeks and 1 year postpartum. Findings to date: A total of 1167 offspring (607 female) born to 703 Generation 2 parents (400 mothers) were recruited into the ATPG3 Study. Findings to date highlight: (1) strong continuities in depressive symptoms and substance use from adolescence through to becoming a parent; (2) a role for persistent preconception mental health problems in risk for parent–child bonding difficulties, as well as infant emotional reactivity and behaviour problems; (3) the importance of secure attachments in adolescence in reducing long-term risk for postpartum mental health problems; and (4) the protective nature of perceived social support, both preconception and postpartum, in strengthening relationship quality and social support during the COVID-19 pandemic. Future plans: Assessments of ATPG3 families in preschool and middle childhood are currently funded and underway. We intend to maintain the offspring cohort through childhood, adolescence, young adulthood and into parenthood. Data will be used to map preconception determinants of emotional health, and enhance approaches to population monitoring and targeted intervention over the life course and across generations.